A Comparison of Pertinence between Containment and Dewey Labelling Schemes to the XML Documents - H. A. Al-khazraji, Samer (University of Thi-Qar Journal, 2024)
Researchers are interested in improving the XML database management system using an indexing system by labelling XML nodes. They proposed many labelling schemes to be equivalent to the indexing system of the relational database management system. There are many algorithms that have been suggested for efficiently assigning labels to XML documents in a small amount of storage space. But, the majority of the models concentrated on assessing the effectiveness of proposed labelling schemes. The pertinence of a labelling technology with a certain pattern of XML database has not been adequately inspected. For analysing this point, several experiments were carried out have been executed to label different XML data structures using Containment and Dewey labelling schemes. The requirements of time and space have been taken into account to measure the relevance of the labelling scheme to a specific structure of XML document. It was discovered that both schemes are relatively efficient when allocating labels for a shallow structure of an XML tree. Both schemes are efficient, however, the former for short tree and the latter for wide tree.